Comparison of two treatments for coxarthrosis: local hyperthermia versus radio electric asymmetrical brain stimulation - Castagna A (Dove Medical Press, 2011)
Alessandro Castagna1, Salvatore Rinaldi1,2, Vania Fontani1, Piero Mannu1, Matteo Lotti Margotti11Rinaldi Fontani Institute, Department of Neuro Psycho Physio Pathology, 2Medical School of Occupational Medicine, University of Florence, Florence, ItalyBackground: It is well known that psychological components are very important in the aging process and may also manifest in psychogenic movement disorders, such as coxarthrosis. This study analyzed the medical records of two similar groups of patients with coxarthrosis (n = 15 in each) who were treated in two different clinics for rehabilitation therapy.Methods: Patients in Group A were treated with a course of traditional physiotherapy, including sessions of local hyperthermia. Group B patients were treated with only a course of radioelectric asymmetrical brain stimulation (REAC) to improve their motor behavior.Results: Group A showed a significant decrease in symptoms of pain and stiffness, and an insignificant improvement in range of motion and muscle bulk. A single patient in this group developed worsened symptoms, and pain did not resolve completely in any patient. The patients in Group B had significantly decreased levels of pain and stiffness, and a significant improvement in range of motion and muscle bulk. No patients worsened in Group B, and the pain resolved completely in one patient.Conclusion: Both treatments were shown to be tolerable and safe. Patients who underwent REAC treatment appeared to have slightly better outcomes, with an appreciable improvement in both their physical and mental states. These aspects are particularly important in the elderly, in whom functional limitation is often associated with or exacerbated by a psychogenic component.Keywords: coxarthrosis, anti-aging, motor behavior, radioelectric asymmetric brain stimulation